Conflict in invasive species management. Issue 3 (13th March 2017) - Crowley, Sarah L; Hinchliffe, Steve; McDonald, Robbie A
Abstract : As invasive species management becomes more ambitious in scope and scale, projects are increasingly challenged by disputes and conflicts among people, which can produce undesirable environmental and social outcomes. Here, we examine when and how conflicts have arisen from invasive species management, and consider why some management approaches may be more prone to conflict than others. Insufficient appreciation of sociopolitical context, non‐existent or perfunctory public and community engagement, and unidirectional communications can all foster "destructive" conflict. We propose that approaches to conflict in invasive species management might be transformed by anticipating disagreements, attending more carefully to the social‐ecological contexts of management, adopting more inclusive engagement mechanisms, and fostering more open, responsive communication. Conflicts may be unavoidable, but they can be anticipated and need not be destructive.